Erectile Dysfunction and Decreased Libido in Klinefelter Syndrome: A Prevalence Meta-Analysis and Meta-Regression Study. Issue 6 (20th May 2021) - Barbonetti, Arcangelo; D'Andrea, Settimio; Vena, Walter; Pizzocaro, Alessandro; Rastrelli, Giulia; Pallotti, Francesco; Condorelli, Rosita; Calogero, Aldo E.; Pasquali, Daniela; Ferlin, Alberto; Foresta, Carlo; Jannini, Emmanuele A.; et al.
ABSTRACT: Background: Only few studies have assessed sexual dysfunction in men with Klinefelter syndrome (KS). Aim: To define pooled prevalence estimates and correlates of erectile dysfunction (ED) and decreased libido (DL) in KS. Methods: A thorough search of Medline, Embase and Web of Science was performed to identify suitable studies. Quality of the articles was scored using the Assessment Tool for Prevalence Studies. Data were combined using random effect models and the between-studies heterogeneity was assessed by the Cochrane's Q and I 2 . The sources of heterogeneity were investigated by meta-regression and sub-group analyses. Funnel plot, Begg's rank correlation and trim-and-fill test were used to assess publication bias. Main Outcome Measure: The pooled prevalence of ED and DL in KS as well as 95% confidence intervals (CIs) were estimated from the proportion of cases of sexual dysfunction and the sample size. Variables that could affect the estimates were identified by linear meta-regression models. RESULTS: Sixteen studies included collectively gave information about ED and DL in 482 and 368 KS men, respectively, resulting in a pooled prevalence of 28% (95% CI: 19%–36%) for ED and 51% (95% CI: 36%–66%) for DL, with a large heterogeneity. The trim-and-fill adjustment for publication bias produced a negligible effect on the pooled estimates. At the meta-regression analyses, a higher prevalence of ED was significantly associated with an older age but not with lower testosterone levels. In series with a mean age >35 years, the ED prevalence estimate increased up to 38% (95% CI: 31%–44%) with no heterogeneity (I 2 =0.0%, P =0.6). On the contrary, the prevalence of DL increased significantly as testosterone levels decreased, without a significant relationship with age. Clinical Implications: While DL would largely reflect an androgen deficiency, in older men with KS, erectile function should be assessed irrespective of testosterone levels. Strength & Limitations: This is the first meta-analysis defining pooled prevalence estimates and correlates of ED and DL in KS. Nevertheless, caution is required when interpreting results, due to the high risk of bias in many studies, as well as the dearth of data about psychosocial and/or psychosexological variables and age at the diagnosis. CONCLUSIONS: ED and DL represent common clinical complaints in KS. While the prevalence of ED would increase with age, DL gets more common as serum testosterone decreases. Further studies are warranted to elucidate the pathogenetic mechanism(s) underlying the age-dependent increase in the prevalence of ED, apparently unrelated to the androgenic status.